2019
DOI: 10.1177/0272431619858420
|View full text |Cite
|
Sign up to set email alerts
|

Coping With the Stresses of Daily Life in England: A Qualitative Study of Self-Care Strategies and Social and Professional Support in Early Adolescence

Abstract: The aim of our study was to examine early adolescents’ perspectives on and experiences of coping with the problems, difficult situations, and feelings that can arise in daily life in England. Our study draws on the first time point of semistructured interviews ( N = 82) conducted with 9 to 12 year olds across six regions of England as part of HeadStart, a mental health and well-being program. Using thematic analysis, eight main themes were derived from the dataset relating to participants’ coping behavior: act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 60 publications
(78 reference statements)
5
24
1
Order By: Relevance
“…Several of the self-management strategies identified in the current study align with previous research investigating coping [6] and non-professionally mediated interventions [5]. Stapley et al [6] identified similar coping strategies, including 'digital or media entertainment', 'creative activities', 'being physically active', 'positive thinking or optimism', 'ignoring people, feelings or situations', 'social support' and 'other professional support' (see Table 1).…”
Section: Specific Self-management Strategiessupporting
confidence: 80%
See 2 more Smart Citations
“…Several of the self-management strategies identified in the current study align with previous research investigating coping [6] and non-professionally mediated interventions [5]. Stapley et al [6] identified similar coping strategies, including 'digital or media entertainment', 'creative activities', 'being physically active', 'positive thinking or optimism', 'ignoring people, feelings or situations', 'social support' and 'other professional support' (see Table 1).…”
Section: Specific Self-management Strategiessupporting
confidence: 80%
“…In the last few decades, self-management has expanded from long-term illness toward youth mental health. The idea of caring for or managing oneself is appearing with increasing frequency in published research [ 5 , 6 ], United Kingdom (UK) policy [ 7 , 8 ] and reports from charities and health bodies [ 9 , 10 ]. This may be due to rising societal awareness of the heightened prevalence of mental health difficulties in young people in the UK (NHS Digital, 2018) and long wait times to access specialist youth mental health support [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they may not be as health conscious as older people are. Moreover, as a recent qualitative study showed, self-care strategies within the young population are mostly based on social media resources [ 36 ], whereas these resources are not being used enough to disseminate adherence to health practices and self-care behavior in these age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may not be as health conscious as older people are. Moreover, as a recent qualitative study showed, self-care strategies within the young population are mostly based on social media resources [38], whereas these resources are not being used enough to disseminate adherence to health practices and self-care behavior in these age groups.…”
Section: Discussionmentioning
confidence: 99%